2004
DOI: 10.1007/978-3-540-28631-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Memories: Beyond Concepts and Techniques for Case Base Maintenance

Abstract: Maintenance of Case-Based Reasoning (CBR) systems became an important area since applications of CBR technologies were established in different real-world domains. Maintenance issues cover all aspects that help to keep a running CBR system in a usable state of high quality. Concepts and techniques that were developed for maintenance of CBR systems range from methodologies and frameworks that particularly define phases, steps, and tasks necessary to integrate maintenance into the CBR process up to specific prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Consequently, architectures and systems have been developed which support this process [3] [14] and also look into the life-time aspect concerned with case-based maintenance. …”
Section: Case-based Reasoning Process Modelmentioning
confidence: 99%
“…Consequently, architectures and systems have been developed which support this process [3] [14] and also look into the life-time aspect concerned with case-based maintenance. …”
Section: Case-based Reasoning Process Modelmentioning
confidence: 99%
“…Figure 3 An extension of the classical 4-stage CBR model to emphasize the importance of maintenance in overall system performance, illustrating the setup, initialization, application and maintenance phases of the SIAM methodology for maintaining CBR systems. Adapted from (Iglezakis et al, 2004).…”
Section: Case-base Maintenancementioning
confidence: 99%
“…Reinartz et al (2001) propose to extend the classic four-stage CBR cycle shown in Figure 1 to include two new steps, a review step to monitor the quality of system knowledge and a restore step which selects and applies maintenance operations. Their revised model, shown in Figure 3, emphasizes the important role of maintenance in modern CBR and indeed proposes that the concept of maintenance encompass the retain, review and restore steps (Iglezakis et al, 2004).…”
Section: Case-base Maintenancementioning
confidence: 99%
“…Items are a uniform representation for knowledge in the sense that all "data", "information" and "knowledge" things are represented in the same way. The insights gained by analysing the maintenance of items leads naturally to an understanding of the maintenance of if-then rules, conventional programs and other knowledge representation paradigms [3]. The integrity of items represented in this model is maintained by following maintenance linksthe structure of these links is simplified by a decomposition process.…”
Section: Introductionmentioning
confidence: 99%